Chemical variables - stream from Erken Catchment, Slumsviken - Erken Laboratory (Uppsala University, 2025)
Manual grab samples from the stream for chemical analysis are taken on a biweekly basis during ice-free conditions, and on a monthly basis in the presence of stream ice.
Erken Laboratory (2025). Chemical variables - stream from Erken Catchment, Slumsviken, 2014-01-14–2023-12-12 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/OqOuNPXrxa8U8O7KaxWibrBL
Keywords: Erken Laboratory; Stream; Time instant; Time instant; pH; pH; Specific conductivity; Specific conductivity; Colour of Water; Colour of Water; Water temperature; Water temperature; Phosphate-P; Phosphate-P; Ammonium-N; Ammonium-N; Total nitrogen; Total nitrogen; Silicon; Silicon; Dissolved organic carbon; Dissolved organic carbon; Total organic carbon; Total organic carbon; Fluorine; Fluorine; Chlorine; Chlorine; Sulphate-S; Sulphate-S; Bromine; Bromine; Aluminium; Aluminium; Boron; Boron; Calcium; Calcium; Iron; Iron; Potassium; Potassium; Magnesium; Magnesium; Manganese; Manganese; Sodium; Sodium; Phosphorus; Phosphorus; Sulfur; Sulfur; Zinc; Zinc; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap